The effects of base station as an electromagnetic radiation source on flower and cone yield and germination percentage in Pinus brutia Ten - Ozel, Halil Baris; Cetin, Mehmet; Sevik, Hakan; Varol, Tugrul; Isik, Berkant; Yaman, Barbaros (Springer Science and Business Media LLC, 2021)
Electromagnetic radiation is a substantial pollution factor that most of the living things found almost everywhere are constantly exposed to with current technology. The number of studies conducted on the effects of this exposed radiation on the living things constantly is limited; and almost all of the studies conducted are aimed at measuring the effects of short-term exposure. In addition to this, most of the studies conducted on plants focus on herbaceous plant species. In this study, the effects of distance to base station on flower and cone yield and germination percentage were investigated in Pinus brutia individuals, one of the critical forest tree species. The study results revealed that being close to the base station significantly reduced the number of flowers and cones in P. brutia individuals, and that the values obtained in individuals at a distance of 800 m from the base station were 11 times more than the number of flowers and 7 times more than the number of cones compared to the individuals at a distance of 100 m. In the seeds subject to the study, there is a three-times difference in terms of the germination percentage among the individuals located at the furthest and closest distance to the base station. These results show that P. brutia individuals are considerably affected by the base station.
Keywords: Base Station; Electromagnetic Radiation; Germination; Pinus; Pinus Brutia Ten; Q1 Science (General) / természettudomány általában; Flower; QH301 Biology / biológia; General Agricultural and Biological Sciences; Cone; 15. Life on land; 13. Climate action